2022
DOI: 10.7554/elife.79018
|View full text |Cite
|
Sign up to set email alerts
|

Centrally expressed Cav3.2 T-type calcium channel is critical for the initiation and maintenance of neuropathic pain

Abstract: Cav3.2 T-type calcium channel is a major molecular actor of neuropathic pain in peripheral sensory neurons, but its involvement at the supra-spinal level is almost unknown. In the Anterior Pretectum (APT), a hub of connectivity of the somatosensory system involved in pain perception, we show that Cav3.2 channels are expressed in a sub-population of GABAergic neurons co-expressing parvalbumin (PV). In these PV-expressing neurons, Cav3.2 channels contribute to a high frequency bursting activity, which is increas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…It is widely acknowledged that PV neurons play a dominating role in pain regulation [53][54] . However, the results of the present study suggested that SST neurons, rather than PV neurons, in the ACC are the major players in pulpitis pain regulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that PV neurons play a dominating role in pain regulation [53][54] . However, the results of the present study suggested that SST neurons, rather than PV neurons, in the ACC are the major players in pulpitis pain regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased voltage-gated sodium channel 1.7 (NaV1.7) expression leads to increased neuronal excitability and ultimately causes neuropathic pain in animal models ( Li et al, 2018 ). In the early stage of nerve injury, the expression of the Cav3.2 channel and functional enhancement of damaged neurons lead to an increase in ectopic discharge frequency ( Fayad et al, 2022 ). Transient receptor potential ankyrin 1 (TRPA1) and transient receptor potential melastatin 8 (TRPM8) knockout mice demonstrated relief of pain sensitization in neuropathic models ( Trevisan et al, 2016 ; de Caro et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…[2,9,10] Moreover, within the nociceptive circuitry encompassing dorsal root ganglion (DRG) neurons, the superficial dorsal horn, and anterior pretectum, Ca v 3.2 is the predominant isoform implicated in numerous intractable painful symptoms. [11][12][13] LVGCCs are attractive drug targets for several serious neurological disorders, such as epilepsy, pain, and essential tremor. [2,14,15] At least eight classes of selective triple LVGCCs blockers (STLBs) have been synthesized, and several candidates, such as CX8998, Z944, and ACT-709478 are currently in phase I or II clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] Cyclovirobuxine D (CVBÀ D), a representative alkaloid of the traditional Chinese medicine B. microphylla and also an in-use cardiovascular drug in China, was initially identified as a potent analgesic agent mainly through inhibition of Ca v 3.2. [22] In this study, we further investigated the Ca v 3.2 inhibition of 23 natural Buxus alkaloids (1-23) with 9,19cyclo-artane-type (1-7), 9(10/19)abeo-artane-type (8)(9)(10)(11)(12)(13)(14)(15)(16), and 17(13/18)abeo-artane-type (17)(18)(19)(20)(21)(22)(23) chemical scaffolds (Figure 1A). Compounds 1-5 and 7 were isolated from B. rugulosa, [26] 6, 8-16, and 23 were purified from B. sempervirens, [27] and 17-22 were identified from B. austroyunnanensis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation